Career Exploration Guidance Service for Indonesian Adolescents: A Literature Review Study - Awaliyah, Annisa Mumtaz; Supriatna, Mamat (Academia Edu Cendekia Indonesia (AEDUCIA), 2022)
In the 21st century, adolescents will experience changing career paths and need the skills to seek information about themselves and the environment, including understanding the ability, interests, and values that will affect career satisfaction and decision-making. To obtain this information, adolescents need the opportunity to be involved in career exploration activities. Career exploration can be developed by guidance and counseling teachers by providing guidance services related to career exploration. This study aims to discuss the development of various guidance services to develop career exploration for adolescents in Indonesia. This research method uses a literature review examining various relevant reference sources related to career exploration based on the last ten years. The results revealed that there were still advantages and disadvantages in implementing career exploration guidance services that can be used as evaluation material in developing career exploration guidance services for adolescents. It can be concluded that the guidance service to develop adolescent career exploration is growing and can help adolescents to develop their career exploration.